ANALISIS LEMBAGA PEMASARAN JAGUNG KUNING DI KECAMATAN BONTOLEMPANGAN KABUPATEN GOWA - Dewi Pratiwi Indriasari (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
Corn is an important food commodity after rice. Based on the sequence of staple foods, corn is a strategic commodity in agricultural development and the Indonesian economy, and has a multipurpose function, both for food and feed, and has balanced nutrition. The problem is whether the involvement of various yellow corn marketing institutions can increase marketing efficiency itself. While the purpose of the author is to see each marketing channel or marketing agency involved so that it can improve marketing efficiency. The most cost-effective marketing channel for marketing is channel III with a value of 6.84%, in this marketing channel the retailer directly buys farmers. Channel II the value of marketing cost efficiency is 9.31% because there are several marketing agencies involved, as well as marketing channels I with marketing cost efficiency value of 12.35%